2001
DOI: 10.3171/spi.2001.94.2.0245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neuroprotective effects of sodium channel blockers after spinal cord injury: improved behavioral and neuroanatomical recovery with riluzole

Abstract: Object. Persistent activation of voltage-sensitive Na+ channels is associated with cellular toxicity and may contribute to the degeneration of neural tissue following traumatic brain and spinal cord injury (SCI). Pharmacological blockade of these channels can attenuate secondary pathophysiology and reduce functional deficits acutely. Methods. To determine the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 85 publications
5
133
1
1
Order By: Relevance
“…In contrast to calcium blockers, significant improvement in neuroprotective function was observed after treatment with sodium channel blockers in rats (Schwartz et al, 2001;Teng et al, 1997). However, similar benefits of treatment with sodium-channel blockers were not observed in few clinical studies.…”
Section: Search Strategymentioning
confidence: 84%
“…In contrast to calcium blockers, significant improvement in neuroprotective function was observed after treatment with sodium channel blockers in rats (Schwartz et al, 2001;Teng et al, 1997). However, similar benefits of treatment with sodium-channel blockers were not observed in few clinical studies.…”
Section: Search Strategymentioning
confidence: 84%
“…Clinicamente, há um grande interesse na utilização de novas terapias, como células tronco (DASARI et al, 2007), ou os bloqueadores de canais iônicos (OLIVEIRA, 2012;LAVOR, 2013), capazes de prevenir ou retardar as complicações neurológicas e, com isso, ampliar a janela terapêutica para outros potenciais agentes neuroprotetores. Dentre os diferentes tratamentos propostos, estão os antiinfl amatórios esteroidais (BARTHOLDI & SCHWAB, 1995;ROSADO, 2011) e não esteroidais (GUTH et al, 2006), bloqueadores de canais para sódio (SCHWARTZ & FEHLINGS, 2001;WU et al, 2013), bloqueadores de canais para cálcio (BCC) (OLIVEIRA, 2012) e anestésicos gerais (FUKUSHIMA, 2012;LAVOR, 2013). Agentes BCC mostram-se especialmente promissores na redução de lesões cerebrais e medulares, por impedir o infl uxo exacerbado desse íon e, assim, prevenir a progressão da lesão secundária (VERWEIJ et al, 1997).…”
Section: Introductionunclassified
“…The neuroprotective agent riluzole, currently in use to treat patients with ALS, has been the focus of eight preclinical studies (Table 1) [3,33,39,43,44,53,55,56]. Its neuroprotective properties are the result of blocking voltage-sensitive sodium channels and antagonism of presynaptic calcium-dependent glutamate release.…”
Section: Questionmentioning
confidence: 99%
“…Epidemiologic research has demonstrated that spinal cord injury (SCI) affects 10 to 40 persons per million population per annum in developed countries such as the United States [53]. This number must be interpreted with reference to a complete picture of this devastating condition: a substantial number of individuals who sustain a SCI die before reaching the hospital; patients who do reach the hospital have complications related to their injury and are at high risk of morbidity and mortality; the economic costs of this injury are estimated in the billions of dollars in developed countries (United States); and the personal and family suffering is incalculable [2,29,54].…”
Section: Introductionmentioning
confidence: 99%